Fourth Five Year Plan 1969-74 and Annual Plan 1969-70 Draft Outline Union Territory of Pondicherry - Planning Commission (Planning Commission, 1996)
The Union lerrilory of Pondicherry comprises the four regions of Pondicherry, Karaikal. Mahe and Yanam, covering an area of about 479.2 sq. kms. with a population of 3.69 lakhs, according to the 1961 census. The Pondicherry region (area 290.1 sq. kms.) is on the east-coast, about 160 kms south of Madras. Pondicherry is not a contiguous area but is interspersed with enclaves of Madras Stale. It consists of 267 villages, with a total popu lalion of 2.59 lakhs. About 160 kms. further south on the east-coast lies the Karaikal region (area 158 sq. kms.) consisting of 118 villages with a population of 81,000.
Finance Department Government of Pondicherry